The interplay between HQ legitimation and subsidiary legitimacy judgments in HQ relocation: A social psychological approach - Balogun, J; Fahy, K; Vaara, E (Palgrave Macmillan, 2017)
This paper marks a departure from the focus on external stakeholders in much research on legitimacy and multinational corporations, adopting a social psychological approach to study how MNCs build internal legitimacy for controversial decisions with their subsidiaries. We explore this through a longitudinal, real-time qualitative case study of a regional office relocation, since office relocations represent rare yet significant strategic decisions. We analyze the interplay between the legitimation strategies of senior managers and subsidiary legitimacy judgments, based in instrumental, relational, and moral considerations, and how the relationship between the two develops over time. From this analysis, we derive inductively a process model that reveals the dynamics of building internal legitimacy with subsidiaries, and how an MNC moves on even in the absence of full legitimacy, when dealing with controversial MNC decisions. The model highlights two important dynamics. The first is a dynamic between legitimation strategies and legitimacy judgments and how this is influenced by local subsidiary contexts. The second is a temporal dynamic in how both the legitimation strategies and legitimacy judgments evolve over time. Our model contributes to research on legitimacy in MNCs, what we know about tensions that characterize MNC–subunit relationships, and research on headquarters relocation.